Inflammation, hypertension, and microRNA and Prostate Cancer. The Prostate Cancer throughout life (PROCA-life) study - Stikbakke, Einar (Cancers, 2022)
Background/Aims: Prostate cancer (PCa) is the most common cancer among men in Norway as well as world-wide, and a major cause of health loss and death with 1.4 million new cases and 375 000 deaths world-wide in 2020. Biological mechanisms involved in PCa development are mainly unknown, but chronic inflammation, one hallmark of cancer development, has been questioned to play a key role in PCa development. This thesis aimed to explore whether markers that may be linked to inflammation, such as high sensitive-C-reactive protein (hs-CRP) and white blood cell count (WBC), systolic and diastolic blood pressure (BP) and miR-24-1-5p, a subtype of microRNA, may play a role in PCa development, recurrence and mortality. Materials and methods: The Prostate Cancer Study throughout Life (PROCA-life) is a population-based cohort study, a sub study of the Tromsø Study and the present thesis includes all men, who were enrolled in the Tromsø Study between 1994 and 2016 (Tromsø 4-7). The procedures were almost identical, and assessments were done by trained research technicians. By linkage to the Cancer Registry of Norway and Norwegian Cause of Death Registry, all PCa cases and death among the participating men were identified. Detailed histopathological and medical records were obtained. Cox proportional hazard regression models were used to study the association between prediagnostic WBC and hs-CRP in serum (Paper I), prediagnostic blood pressure (Paper II) and PCa risk and prognosis. We collected prostatectomy tissue from 142 PCa patients, and we studied the influence of miR-24-1-5p regarding aggressiveness and prognosis in men diagnosed with PCa. Results: We observed a positive dose-response relationship between hs-CRP and PCa risk. Men with an increase in hs-CRP between two measurements had a 36% increased risk of PCa, compared to men with no change or decrease in hs-CRP. Men with a high systemic inflammatory score (combination of WBC and hs-CRP) had a 68% higher risk of being diagnosed with metastatic disease compared to men ...